Adsorption of carbon dioxide by activated carbon modified with mixture of cu/zn - Bayesti, Iman (2013)
Because of the greenhouse effect, removal of carbon dioxide has become an important topic nowadays. In this study a fixed–bed column has been designed to adsorb the CO2 from the mixture of CO2/He. The adsorption characteristics of carbon dioxide on powder activated carbon have been measured over the temperature range of (30 to 50˚C) at pressure up to 200 kPa in concentrations of CO2 in ranging from 5 to 50%.The commercial activated carbon was modified by impregnation of binary mixture of Cu/Zn with loading ranging from 4 to 20 %. The modification with mixture of Cu/Zn had significantly increased the adsorption capacity of CO2. Also the breakthrough curves for single and mixture metals demonstrates that the CO2 adsorption is higher when the modification is carried out when the mixture of Cu/Zn rather than single metals. The reason that pre-treatment is used is because the acid treatment affect the metal loading. The amount of metal loaded on the HNO3 treated sample (HAC) is more than the original activated carbon (AC) sample. The adsorption capacity for original activated carbon in the temperature of 30˚C, pressure of 100 kPa and 15% concentration of CO2 is 1.52 mol/ kg and after 20% of metal loading the capacity increased to 2.25 mol/ kg. The adsorption capacity decreased with increasing temperature, while increasing the CO2 inlet concentration increase the amount of adsorption capacity. The adsorption capacity decreased with increasing temperature, while increasing the CO2 inlet concentration increase of adsorption capacity. The adsorption capacity increased from 2.33 mol/kg at 150 kPa to 3.61 mol/kg at 200kPa. The deactivation model (DM) derived using the analogy between the adsorption of CO2 and the deactivation of catalyst particles. Observed adsorption rate constants (KS) and first-order deactivation rate constants (Kd) were obtained from the model. It was found that the deactivation model describes the experimental breakthrough curves very well. The isotherm was fitted well with either the Toth or Freundlich equation.